Performance evaluation of transit signal priorities on bus transit corridor based on data envelopment analysis - Yue Qiu; Linghan Zheng; Yuchuan Du; Shengchuan Jiang (International Journal of Transportation Science and Technology, 2020)
Transit Signal Priorities (TSP) is a common control strategy at signalized intersections in Bus Transit Corridors (BTC). Performance pre-evaluation for the TSP is usually based on simulation assessment models and analytical assessment models in order to delineate the scope of TSP projects. However, existing assessment models tend to ignore the overall systematic evaluation. This paper proposes a new method based on data envelopment analysis (DEA) model to evaluate the system-wide effect of TSP on a BTC, considering probability of triggering TSP and the influence of coordinating signal control. Numerical experiments based on the bus operation data from Xizang Road, Shanghai, China are presented to demonstrate effectiveness of the proposed evaluation model. Investment strategy based on the proposed evaluation model on 20 signalized intersections are discussed under different budget limits.